Viral population dynamics and host reprogramming: Insights into grapevine leaf mottling and deformation disease (GLMD) development - Nadia Bertazzon; Luca Nerva; Giorgio Gambino; Walter Chitarra; Elisa Angelini (Plant Stress)
Grapevine Pinot gris virus (GPGV) is an emerging grapevine virus associated with the grapevine leaf mottling and deformation disease (GLMD). The virus consists of genetically distinct variants, with the more virulent forms causing severe disease and the latent ones linked to mild or asymptomatic infections. However, the existence of mixed infections with different viral strains could affect the molecular interplay between the virus and its host plant and determine the disease outbreak. Here, the physiological and molecular mechanisms underlying disease manifestation were investigated in plants obtained from the graft of GPGV-infected materials originated from symptomatic and asymptomatic vines. All grafted plants carried a mixed population of GPGV virulent and latent isolates, and the symptom expression did not consistently match the source. Leaves and roots within a plant harboured different GPGV population. Higher accumulation of virulent GPGV isolates in leaves redirected the host energy and nutritional resources towards viral replication and assembly. This shift negatively affected plant physiological processes and development, independently of GLMD disease. On the opposite, GLMD symptomatic plants showed the lowest accumulation of the latent GPGV isolates in roots, where transcriptomic profiling reveals impaired secondary cell wall maturation. Interestingly, intrahost virus-virus interactions, occurring between GPGV and the grapevine rupestris stem pitting-associated virus (GRSPaV), could rearrange the population of GPGV variants with a possible key role in the disease outbreak.